An Analysis of Types of Teacher's Questions in The English Learning Process in Higher Education - Dian Anggraini; Noni Febriana; Asma Alhusna; Desi Andriani (Jurnal Ilmiah Pendidikan Scholastic, 2023)
This research discusses the types of questions lecturers use in the teaching and learning process for the students of the University of Putra IndonesiaYPTK Padang. The aim of this research is to identify the types of questions generated by lecturers in classroom interactions. This research was carried out on students majoring in Management. In collecting data, researchers used observation and interviews. Observations are used to see the types of questions used by lecturers in the teaching and learning process. Meanwhile, interviews are used to find out why lecturers used the questions in the teaching and learning process. The researcher made observations using an observation checklist, field notes, and a video recorder as tools during the observation. Teacher questions were analyzed using the Miles and Huberman (1995) qualitative data analysis model. The research results show that in the process of learning English in Management classes, teachers predominantly use procedural and convergent types of questions to interact with students. These questions are used to determine the level of students' understanding of the material that has been taught and can help students to recall the material. Using these questions can help students participate actively by responding to these questions. Lecturers do not use divergent types of questions which can increase students' thinking patterns to be more critical in conveying ideas or opinions about something.